Clinical Holistic Medicine: The Case Story of Anna. II. Patient Diary as a Tool in Treatment - Sören Ventegodt; Birgitte Clausen; Joav Merrick (The Scientific World Journal)
In spite of extreme childhood sexual and violent abuse, a 22-year-old young woman, Anna, healed during holistic existential therapy. New and highly confrontational therapeutic tools were developed and used to help this patient (like acceptance through touch and acupressure through the vagina). Her vulva and introitus were scarred from repeated brutal rape, as was the interior of her mouth. During therapy, these scars were gently contacted and the negative emotional contents released. The healing was in accordance with the advanced holistic medical toolbox that uses (1) love, (2) trust, (3) holding, and (4) helping the patient to process and integrate old traumas.The case story clearly revealed the philosophical adjustments that Anna made during treatment in response to the severe childhood abuse. These adjustments are demonstrated by her diary, where sentences contain both the feelings and thoughts of the painful present (the gestalt) at the time of the abuse, thus containing the essence of the traumas, making the repression of the painful emotions possible through the change in the patients philosophical perspective. Anna's case gives a unique insight into the process of traumatization (pathogenesis) and the process of healing (salutogenesis). At the end of the healing, Anna reconnected her existence to the outer world in a deep existential, suicidal crisis and faced her choice of life or death. She decided to live and, in this process, assumed existential responsibility, which made her able to step out of her mental disease. The advanced holistic toolbox seems to help patients heal even from the worst childhood abuse. In spite of the depth of the existential crisis, holistic existential therapy seems to support existential responsibility well and thus safe for the patients.